2017
DOI: 10.1186/s12955-017-0760-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Vascular quality of life questionnaire – 6 for clinical use in patients with lower limb peripheral arterial disease

Abstract: BackgroundThe VascuQoL-6 (VQ-6) health-related quality of life questionnaire, a short version of the disease-specific VascuQoL-25, was developed for clinical practice and use in vascular registries. The study purpose was to evaluate the validity and reliability of VQ-6.MethodsVQ-6 was translated to Norwegian with linguistic validation and face value evaluation, and consecutive patients with intermittent claudication (IC) or critical limb ischemia (CLI) were included. All patients completed VQ-6 and Short Form-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 33 publications
(34 reference statements)
2
35
0
Order By: Relevance
“…To use the self-reported health status, SF-36 item 2, after one year to estimate MID will probably be wrong, as the recall bias will be too large. But, the improvement in VQ-6 summary score for the "unchanged" group (2.3) supports that the earlier proposal of two points of change as indicative and four points as a certain change [4].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…To use the self-reported health status, SF-36 item 2, after one year to estimate MID will probably be wrong, as the recall bias will be too large. But, the improvement in VQ-6 summary score for the "unchanged" group (2.3) supports that the earlier proposal of two points of change as indicative and four points as a certain change [4].…”
Section: Discussionsupporting
confidence: 82%
“…A population-based study from the Swedish national vascular registry, Swedvasc, has indicated 1.7-2.2 scale steps as a minimally important difference (MID), and 3.5-4.5 scale steps as a substantial clinical benefit [7]. MID was estimated using two different methods in the validation study [4]. One method (0.5 SD) gave a value of 1.725 scale points, the other (95%CI) 0.82 for improvement and − 1.38 for deterioration [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations